A new review of the topography and typology of the Danubian Horsemen lead icons in the south-eastern part of Pannonia inferior - Plemić Bojana B.; Crnobrnja Adam N. (Starinar, 2022)
Although the artefacts belonging to the so-called Danubian Horsemen cult have been scientifically examined from various standpoints, the definitive answers to the question of their nature have not yet been reached. One of the key reasons that can be distinguished with regard to this is the lack of insight into the archaeological context since, in comparison to the total number of these artefacts, a small percentage of the samples have been found during archaeological excavations. As the more recent corpora of lead icons points to the conclusion that a significant number originates from the area of the province of Pannonia Inferior, especially its south-eastern part (today`s Srem, Mačva and Posavina), in this paper we have tried to establish at least the widest context they belonged to. Thus, based on the place where they were found, and considering the basic features of the site where it was possible, we investigated whether they belonged to a settlement, necropolis or military setting. Consequently, we concluded that the civil context was dominant in this geographic area in the case of the finds of the so-called Danubian Horseman cult, while we also determined which type of icons were the most prevalent. As the concentration of the lead plaques in this area surpasses the other Danubian provinces, we recognise new possibilities for the interpretation of their function as well as the dating of particular series.